ExoMol line lists – L: high-resolution line lists of H3+, H2D+, D2H+, and D3+. Issue 4 (9th January 2023) - Bowesman, Charles A; Mizus, Irina I; Zobov, Nikolay F; Polyansky, Oleg L; Sarka, János; Poirier, Bill; Pezzella, Marco; Yurchenko, Sergei N; Tennyson, Jonathan
ABSTRACT: New MiZo line lists are presented for the D2 H + and D_3^+ isotopologues of H_3^+ . These line lists plus the existing H_3^+ MiZATeP and the ST H2 D + line lists are updated using empirical energy levels generated using the marvel procedure for H_3^+, H2 D +, and D2 H +, and effective Hamiltonian energies for D_3^+ for which there is significantly less laboratory data available. These updates allow accurate frequencies for far infrared lines for these species to be predicted. Assignments of the energy levels of H_3^+ and D_3^+ are extended using a combination of high accuracy variational calculations and analysis of transition intensities. All line lists are made av ailable via www.exomol.com .